2016
DOI: 10.1016/j.exer.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The lens regenerative competency of limbal vs. central regions of mature Xenopus cornea epithelium

Abstract: The frog, Xenopus laevis, is capable of completely regenerating a lens from the cornea epithelium. Because this ability appears to be limited to the larval stages of Xenopus, virtually all the work to understand the mechanisms regulating this process has been limited to pre-metamorphic tadpoles. It has been reported that the post-metamorphic cornea is competent to regenerate under experimental conditions, despite the fact that the in vivo capacity to regenerate is lost; however, that work didn’t examine the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Nevertheless, adult frogs in vivo are unable to regenerate whole lenses except when the lens capsule is left intact and lens epithelial cells attached to it provide a source for re-growth, as is the case in mammals (see next section; Call et al, 2004; Yoshii et al, 2007; Lin et al, 2016). However, Hamilton and Henry (2016) have recently shown that post-metamorphic corneal in vitro explants can initiate the formation of lens cells via the activation of limbal stem cells and transit amplifying cells of the cornea.…”
Section: The Other Regenerators …mentioning
confidence: 99%
“…Nevertheless, adult frogs in vivo are unable to regenerate whole lenses except when the lens capsule is left intact and lens epithelial cells attached to it provide a source for re-growth, as is the case in mammals (see next section; Call et al, 2004; Yoshii et al, 2007; Lin et al, 2016). However, Hamilton and Henry (2016) have recently shown that post-metamorphic corneal in vitro explants can initiate the formation of lens cells via the activation of limbal stem cells and transit amplifying cells of the cornea.…”
Section: The Other Regenerators …mentioning
confidence: 99%
“…The long chase period, on the other hand, provides an insight into how long the newly generated progeny of the dividing cells persist in the tissue. This approach identifies “label-retaining cells” that are capable of surviving for extended periods of time after having undergone cell division and are either post-mitotic or divide infrequently (Hamilton and Henry, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…These differences may be related to the species being studied or the developmental age of the tissues that were examined. Studies reveal that putative CESCs are present throughout the cornea during early development, being more highly restricted to the periphery at later developmental stages (Davies et al, 2009;Hamilton & Henry, 2016;Pajoohesh-Ganji, Ghosh, & Stepp, 2004). Some insight into the role of the surrounding cellular niche was gained when rabbit cornea epithelial cells were recombined with mouse embryonic dermis.…”
Section: Stem Cell Nichesmentioning
confidence: 99%